Assessment of corticosteroid use as a marker of quality-of-care in the management of inflammatory bowel disease - Quera, Rodrigo (2024)
Introduction: Despite advancements in therapeutic strategies, corticosteroids continue to play a role in inducing remission in Inflammatory Bowel Disease (IBD). Unfortunately, these drugs are often misused. Objectives: To assess the dose and duration of corticosteroid therapy, and the subsequent change in treatment among patients with IBD. Materials and methods: We conducted a descriptive, retrospective observational study on patients with IBD under follow-up at the IBD Program of Clínica Universidad de los Andes from January 2021 to August 2022. Results: Four hundred and thirty-two IBD were included, with 63% being women, with a median age of 42 years (14-94), 66% had ulcerative colitis (UC). Sixty-six percentage of patients had received corticosteroids during the course of their disease (range 1-9 times) for a median duration of 12 weeks (2-48 weeks), with prednisone being the most frequently used corticosteroids (53%). Seventy-seven percentage of patients had received treatment for over 3 months or in supratherapeutic doses (prednisone > 60 mg day). There was a change in the treatment after the use of corticosteroid in 28% of patients compared to 90% after entering the program (p<0.001, CI95%: 1.83-2.49). During the Program’s follow-up, 10% received corticosteroids (71% prednisone, 29% budesonide) with no variations based on IBD type, gender, age, or treatment. No patient received corticosteroids for over 3 months or in supratherapeutic doses in our IBD Program. Conclusion: This study emphasizes the importance of evaluating corticosteroids use as a quality-of -care marker in IBD. The management of these patients through a specialized program could mitigate the excessive use of these drugs.